Rainwater harvesting technologies in the Sahelian zone of West Africa and the potential for outscaling - Barry, Boubacar; Olaleye, Adesola O.; Zougmoré, Robert B.; Fatondji, D. (International Water Management Institute, 2008)
In West Africa, especially in the Sahelian countries of Burkina Faso, Niger, Mali and Mauritania, erratic rainfall sequences within and between years has often led to a high uncertainty in rainfed crop production. Over the past three decades, severe food shortages attributed to drought have been frequently reported in several Sahelian countries, most of which are amongst the least developed of the world. Innovative and indigenous ways to achieve improved crop yields through integrated land and water management such as rainwater harvesting and soil water conservation have been successfully tested and, in some cases, adopted in West Africa. This paper highlights the successful interventions of improved indigenous rainwater harvesting/soil water conservation technologies such as Za? or tassa, stone rows and half-moon in the Sahelian zones of West Africa over the past 10 years, and their contributions to enhancing food security and alleviating poverty. The potential for adoption of these technologies at the farm level and their outscaling to areas with similar agroecological zones are also discussed.